Analisis Kemampuan Problem Solving Berdasarkan Teori Polya Dalam Menyelesaikan Soal Cerita Open-Ended Siswa Sekolah Dasar - Amanda Dwi Yanti; Iis Resyabella; Wulan Exssel Auliya; Melva Septiya Maharani; Rissa Prima Kurniawati (Prosiding Konferensi Ilmiah Dasar, 2026)
Problem-solving ability is one of the essential competencies that students should develop in mathematics learning. However, many students still experience difficulties in solving problems that require reasoning and the application of various solution strategies. This study aimed to analyze elementary school students' problem-solving abilities in solving open-ended word problems based on Polya's theory. This research employed a descriptive qualitative approach involving four sixth-grade students of SDN Sogo 01 as the research subjects. Data were collected through a written test consisting of one open-ended word problem, and the results were analyzed based on Polya's four stages of problem solving: understanding the problem, devising a plan, carrying out the plan, and looking back. The findings revealed that all participants were able to understand the problem and successfully implement their solution plans. At the devising a plan stage, three participants were able to develop systematic solution strategies and apply more than one solution method, while one participant was less accurate in selecting an appropriate strategy. At the looking-back stage, three participants verified their solutions, whereas one participant did not complete the verification process. Therefore, the students' problem-solving abilities based on Polya's theory were generally categorized as good. Nevertheless, students still require further practice in developing systematic solution strategies and verifying both the problem-solving process and the final solutions, particularly when solving open-ended word problems